Density and Distribution Pattern of Lola Snail (Trocus niloticus) in the Coastal Waters of Malaku Village, Central Maluku - Ode, Inem; Sangadji, Madehusen; Tuahuns, Wijayanti (Fakultas Pertanian Universitas Darussalam Ambon, 2024)
The lola snail (Trochus niloticus) is a species of sea snail that has important economic value. This research aims to determine the density and distribution patterns of lola snails in the coastal waters of Malaku Village, Central Maluku. Sampling used a stratified random sampling method with line transects, the research location was divided into 3 stations. Stations I and III have plank coral substrates and dead coral fragments, while station II has rocky substrates and coral flats. The results of the research found that the total number of lola snail individuals found at the research location was 110 individuals spread across 3 research stations. The maximum size of lola snails found was 99.41 mm in diameter and the minimum size found was 47.18 mm in diameter. The highest density of Lola snails at each research station was 0.08 ind/m2 and the lowest was 0.05 ind/m2. The distribution pattern of Lola snails at the research location is a clustered pattern.